2017
DOI: 10.1007/s00439-017-1773-z
|View full text |Cite|
|
Sign up to set email alerts
|

The study of human Y chromosome variation through ancient DNA

Abstract: High throughput sequencing methods have completely transformed the study of human Y chromosome variation by offering a genome-scale view on genetic variation retrieved from ancient human remains in context of a growing number of high coverage whole Y chromosome sequence data from living populations from across the world. The ancient Y chromosome sequences are providing us the first exciting glimpses into the past variation of male-specific compartment of the genome and the opportunity to evaluate models based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 97 publications
(240 reference statements)
5
38
0
1
Order By: Relevance
“…Together with its inheritance from father to son, it is a highly informative marker for the paternal origin of species, populations or individuals with a much stronger phylogeographic differentiation than observed for mitochondrial or autosomal DNA. The highly informative Y-chromosomal markers are now widely exploited in population-genetic studies of humans (Jobling and Tyler-Smith, 2017; Kivisild, 2017), cattle (Edwards et al, 2011; Xia et al, 2019), horse (Wallner et al, 2017; Wutke et al, 2018; Felkel et al, 2019a) water buffalo (Zhang et al, 2016), sheep (Meadows and Kijas, 2009; Zhang et al, 2014), camel (Felkel et al, 2019b), pigs (Guirao-Rico et al, 2018) and dogs (Natanaelsson et al, 2006; Oetjens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Together with its inheritance from father to son, it is a highly informative marker for the paternal origin of species, populations or individuals with a much stronger phylogeographic differentiation than observed for mitochondrial or autosomal DNA. The highly informative Y-chromosomal markers are now widely exploited in population-genetic studies of humans (Jobling and Tyler-Smith, 2017; Kivisild, 2017), cattle (Edwards et al, 2011; Xia et al, 2019), horse (Wallner et al, 2017; Wutke et al, 2018; Felkel et al, 2019a) water buffalo (Zhang et al, 2016), sheep (Meadows and Kijas, 2009; Zhang et al, 2014), camel (Felkel et al, 2019b), pigs (Guirao-Rico et al, 2018) and dogs (Natanaelsson et al, 2006; Oetjens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The sequence was classified as haplogroup Q1b1a1 since it carries derived alleles at the defining SNPs L275 and L612. This lineage, which has not been previously reported in Native Americans, occurs at high frequency in Central, West, and South Asia (Balanovsky et al 2017), and the estimates of the divergence between Q1a and Q1b are around 30-32 kya (Kivisild 2017;Poznik et al 2016). However, based on the sequence of just one individual it is difficult to determine if this lineage can be considered autochthonous in Native Americans, or if instead it reflects post-contact admixture.…”
Section: Resultsmentioning
confidence: 52%
“…The timing and distribution of J1a2b‐P58 were associated with demic expansion of Neolithic agriculturalists and hunter‐gatherers into the Arabian Peninsula from the fertile‐crescent (Al‐Zahery et al, ; Chiaroni et al, ). However, its near absence in ancient Neolithic Europeans, including those from Portugal (Martiniano, Cassidy, & O'Maolduin, ), together with its rise in frequencies in West Eurasia during and after the Bronze Age, suggest instead that its dispersion in Europe was mediated by other different migration episodes of the continent demographic history (Jobling & Tyler‐Smith, ; Kivisild, ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on modern DNA studies, J2‐M172 was mainly observed in the Fertile Crescent, and for many years it was considered the most paradigmatic Y‐chromosome lineage to have spread across Europe with agriculture (Chiaroni et al, ; Semino et al, ). However, ancient DNA studies have revealed that J2 is only sporadically detected in early farmers from the Middle East, and thus far is nearly absent in European Neolithic remains, indicating that haplogroup G2 was instead the most likely lineage to have been widely disseminated by the earliest farmers during the spread of agriculture (Gamba et al, ; HofmanovĂĄ et al, ; Jobling & Tyler‐Smith, ; Kivisild, ; Mathieson et al, ; Pereira et al, ; Sikora et al, ). The other main sub‐haplogroup is J1‐M267, whose origin is more unclear.…”
Section: Introductionmentioning
confidence: 99%